ECOLOGICAL NICHE MODELLING OF HIMALAYAN LANGUR (Semnopithecus entellus) IN SOUTHERN FLANK OF THE HIMALAYA - Khanal, Laxman; Chalise, Mukesh Kumar; Jiang, Xuelong (Journal of Institute of Science and Technology, 2018)
The species and subspecies status of various populations of the Himalayan langur (Semnopithecus entellus) have been disputed in many literatures. Before delineating the taxonomic boundaries, it is important to identify the potential distribution areas of extant populations of the species. Ecological niche modeling (ENM) can be coupled with the systematic survey of species presence to identify the species’ potential distribution range. Therefore, we did extensive survey and population census of the Himalayan langur across three major river basins (Koshi, Gandaki and Karnali) of Nepal and analyzed the population patterns. In addition, we also modelled the ecological niche of the species by using maximum entropy (MaxEnt) algorithm. We counted a total of 559 individuals from 33 troops that accounted the average troop size of 16.94 (±8.39) individuals. Within Nepal territory, the highest population of langurs was observed from the Gandaki River basin followed by the Karnali River basin. We revealed that Himalayan langurs have a wide range of altitudinal (49 m - 4190 m above sea level) distributions from Bhutan to Kashmir across southern flank of the Himalaya. We warrant for the detail distribution assessment and taxonomic analysis of Himalayan langurs using ecological, morphological and genetic variables.